Ejected Particles after Impact Splash on Mars: Electrification - T. Becker; F. C. Onyeagusi; J. Teiser; T. Jardiel; M. Peiteado; O. Muñoz; J. Martikainen; J. C. Gomez Martin; J. Merrison; G. Wurm (The Planetary Science Journal, 2024)
Within the RoadMap project, we investigated the microphysical aspects of particle collisions during saltation on the Martian surface in laboratory experiments. In earlier works, we followed the size distribution of ejected particles, their aerodynamic properties, and aggregation status upon ejection. We now focus on the electrification and charge distribution of ejected particles. We analyzed rebound and ejection trajectories of grains in a vacuum setup with a strong electric field of 100 kV m ^−1 and deduced particle charges from their acceleration. The ejected particles have sizes of about 10–100 μ m. They carry charges up to 10 ^5 e or charge densities up to >10 ^7 e mm ^−2 .